NEW PATTERNS OF PALM LICENSING EXPANSION: ACCESS AND POWER RELATIONS IN FOREST AREAS IN INDONESIA - Nur Asih, Sani; Andreas, Rico; Yudhi, Rifka; Alfian, Fajar Bima (Faculty of Law Sriwijaya University, 2023)
Indonesia is one of the most significant palm oil contributors in the world. Palm oil is one of the leading commodities supporting the running of Indonesia's national economy. The high influence of the economic growth of oil palm in Indonesia has caused a shift in the cultivation of rubber and other conventional cash crops at the community level, changing to oil palm regardless of the role of oil palm in the nation's economy. The oil palm plantation industry is not welcomed by some Indonesian people affected by oil palm plantations. This is because the practice of oil palm plantations in Indonesia is suspected as one of the triggers for various environmental and social problems, such as deforestation, clearing of peatlands, forest fires, loss of biodiversity, and tenure conflicts. The issues to be discussed are, first, how the permits are granted to the palm oil industry in forest areas by the government; second, what control strategy must be carried out against the palm oil industry in Indonesian forest areas. This research was conducted using the socio-legal research method. Without an accountable and strict control system in the licensing process, it will impact the large number of oil palm plantation permits issued that tend to violate spatial regulations. Apart from that, further regulation of policies regarding palm oil in the work copyright law will increase the length of conflicts that occur and complicate reforming palm oil governance. Applying the